Effects of different lower limb movement velocities on trunk muscle activity and dynamic stability in the Sahrmann core stability test - Kohei Yoshikawa; Matsuri Hashimoto; Rina Murata; Yuta Murata; Takumi Jiroumaru; Noriyuki Kida (PLoS ONE, 2025)
Core stability is essential for both performance and rehabilitation, yet standardized movement velocity criteria for the Sahrmann Core Stability Test (SCST) remain undefined. This study aimed to analyze how lower limb movement velocity affects trunk muscle activation patterns across movement phases and sides during SCST Level 3 in a supine position. SCST Level 3 was selected because it challenges both deep and superficial muscles without being too difficult for healthy participants. Sixteen healthy adult males, recreationally active but not involved in a training program at the time of recruitment, performed leg-lowering movements at three velocities: slow (5 s), medium (3 s), and fast (1 s). Surface electromyography recorded activation in the internal oblique/transversus abdominis (IO/TrA), external oblique (EO), and rectus abdominis (RA). Dynamic stability was simultaneously monitored using an inflatable pressure-biofeedback unit positioned at L4–L5 and inflated to 40 mmHg; participants maintained the pressure within ±10 mmHg throughout each trial. Muscle activity was analyzed across five phases: 500 ms and 250 ms before movement (pre-500 ms, pre-250 ms), and three post-movement phases (post 1, post 2, post 3). A three-way repeated-measures ANOVA (factors: velocity, movement phase, and laterality) revealed significant velocity-phase interactions for all muscles (p < 0.05; IO/TrA: η2 = 0.170; EO: η2 = 0.198; RA: η2 = 0.153), indicating that velocity affected the temporal activation pattern, particularly during the middle phase of the movement. Faster movements led to a rapid increase in IO/TrA, EO, and RA activity at post 2, whereas slower movements showed a gradual increase. Activation levels converged across conditions by the final phase, with no significant differences between deep and superficial muscles or between sides. These findings suggest SCST Level 3 consistently elicits high trunk muscle activation regardless of velocity. However, faster movements may provide valuable insights into trunk stabilization during mid-movement for clinical evaluations.